Undergraduates Phenotyping Arabidopsis Knockouts in a Course-Based Undergraduate Research Experience: Exploring Plant Fitness and Vigor Using Quantitative Phenotyping Methods - Murren, Courtney J. (J Microbiol Biol Educ, 2019)
We present a curriculum description, an initial student outcome investigation, and sample scientific results for a representative Course-Based Undergraduate Research Experience (CURE) that is part of the “Undergraduates Phenotyping Arabidopsis Knockouts” (unPAK) network. CUREs in the unPAK network characterize quantitative phenotypes of the model plant Arabidopsis from across environments to uncover connections between genotype and phenotype. Students in unPAK CUREs grow plants in a replicated block design and make quantitative measurements throughout the semester. This CURE enables students to answer plant science questions that draw from fields such as environmental science, genetics, ecology, and evolution. Findings indicate that this experience provides students with opportunities to make relevant scientific discoveries. Eighty percent of student datasets produced from the CURE met criteria for inclusion in the project database, indicative of student learning in data collection and analysis of quantitative plant traits. Student datasets uncovered novel effects of mutation on plant form. In addition, students’ science self-efficacy increased as a result of course participation, and faculty feedback on course implementation was positive. We present unPAK as a new network that supports CUREs and research experiences focused on collecting biological data made publicly available to the scientific community. The unPAK CUREs can be tailored to address instructor interests or pedagogical needs while involving students in research investigating quantitative plant phenotypes.